2014
DOI: 10.1038/ejcn.2014.60
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and industry self-regulation of food and beverage marketing: a literature review

Abstract: Although the reviewed studies vary in terms of analytic units and methods applied, they generally stress an ineffectiveness of existing self-regulation schemes. Food industry self-regulation in relation to obesity prevention is an emerging field of research, and further research is needed in such schemes' definitions of regulatory standards, their monitoring and sanctioning mechanisms, and their interactions with public regulation, if industry self-regulation of marketing behaviour is to become an effective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 41 publications
5
59
0
Order By: Relevance
“…This is aligned with other systematic review evidence showing that industry self‐regulation has not been effective in reducing children's exposures to unhealthy food marketing . Limitations of industry codes of practice for responsible marketing have been well documented . Such codes have limited impact because of their voluntary adoption, variation in applications across countries, inadequate or vague definitions for when and where food marketing to children can occur, and permissive nutrient criteria on which to base foods deemed acceptable to be promoted .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This is aligned with other systematic review evidence showing that industry self‐regulation has not been effective in reducing children's exposures to unhealthy food marketing . Limitations of industry codes of practice for responsible marketing have been well documented . Such codes have limited impact because of their voluntary adoption, variation in applications across countries, inadequate or vague definitions for when and where food marketing to children can occur, and permissive nutrient criteria on which to base foods deemed acceptable to be promoted .…”
Section: Discussionsupporting
confidence: 69%
“…38 Limitations of industry codes of practice for responsible marketing have been well documented. 13,14,39 Such codes have limited impact because of their voluntary adoption, variation in applications across countries, inadequate or vague definitions for when and where food marketing to children can occur, and permissive nutrient criteria on which to base foods deemed acceptable to be promoted. 40 Industry self-regulatory codes do not apply any universal or independently developed nutrient profiling model for identifying foods that may be advertised to children, such as the WHO Regional Office for Europe model used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Still, companies have incentives to join, because they solidify a scheme and thus avoid public regulation, they become accepted among peer companies and they enjoy reputational benefits of being associated with the scheme. An emerging field of research in food industry self-regulation with regard to obesity prevention 12,13 is showing somewhat mixed results regarding the effectiveness of such self-regulation schemes in reducing children's exposure to marketing of unhealthy foods and beverages. [14][15][16][17] A number of major international companies have signed the so-called EU Pledge, as a collective self-regulation initiative establishing a code of conduct for marketing activities directed towards children (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A literature review has found that Coca‐Cola is no different than other players in the food and beverage industry in that self‐regulation has been largely ineffective in combating obesity. Issues such as the establishment of low or vague standards, loopholes, and voluntary participation have hindered real progress (Ronit & Jensen, ). Many argue that some degree of outside regulation is necessary because the conflicts of interest are too great to overcome (Ronit & Jensen, ; Mukherjee & Ekanayake, ).…”
Section: Discussionmentioning
confidence: 99%